Enhancing sport performance through athlete health and well-being - Mountjoy, M. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The aquatic athlete can enjoy improved health from sport participation. Swimming is a sport that can be enjoyed recreationally long after retirement from competitive sport. Participation in elite sport however, is not without physical and psychological risks, and as members of the athlete entourage, we are obligated to ensure that our sport environment is as safe as feasible for our athletes. Involvement in high performance aquatic sport has unique health risks. These risks include overuse and traumatic injuries as well as sport-related illnesses. Research in aquatic sport medicine and sport science has been conducted to address these risks. Through the application of the outcomes of this research, these injuries and illnesses can be prevented and/or mitigated to improve both athlete health and performance. FINA, as the sport governing International Federation, is mandated by the Fundamental Principles of Olympism, and the FINA Rules to take measures to protect the health and well-being of the aquatic athlete. FINA has undertaken scientific research and implemented intervention programs to improve the health of the aquatic athlete. There are health issues that are common to all of the aquatic disciplines, and others that are sport-discipline specific. Members of the sport entourage can play an active role in the health promotion of the aquatic athlete by i) employing prevention measures, ii) being vigilant for early signs of health concerns, and iii) implementing appropriate treatment interventions and return to play principles.